2022
DOI: 10.3389/fimmu.2022.809261
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Signaling Deregulation Induces Myeloid-Derived Suppressor Cells in T-Cell Acute Lymphoblastic Leukemia

Abstract: Notch receptors deeply influence T-cell development and differentiation, and their dysregulation represents a frequent causative event in “T-cell acute lymphoblastic leukemia” (T-ALL). “Myeloid-derived suppressor cells” (MDSCs) inhibit host immune responses in the tumor environment, favoring cancer progression, as reported in solid and hematologic tumors, with the notable exception of T-ALL. Here, we prove that Notch-signaling deregulation in immature T cells promotes CD11b+Gr-1+ MDSCs in the Notch3-transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Conversely, anti-Gr1-mediated depletion of MDSCs in T-ALL-bearing mice significantly reduced the proliferation and expansion of malignant T-cell. These data were confirmed by coculturing human Notch-dependent T-ALL cell lines and healthy donor derived PB mononuclear cells in vitro , resulting in increased CD14 + HLA-DR low/neg MDSC accumulation and T-cell suppression; effects that were not observed with T-ALL cells that did not express Notch1- or Notch3-activated protein ( 79 ).…”
Section: Therapeutic Approaches To Target Mdsc In Hematological Cancersmentioning
confidence: 76%
See 1 more Smart Citation
“…Conversely, anti-Gr1-mediated depletion of MDSCs in T-ALL-bearing mice significantly reduced the proliferation and expansion of malignant T-cell. These data were confirmed by coculturing human Notch-dependent T-ALL cell lines and healthy donor derived PB mononuclear cells in vitro , resulting in increased CD14 + HLA-DR low/neg MDSC accumulation and T-cell suppression; effects that were not observed with T-ALL cells that did not express Notch1- or Notch3-activated protein ( 79 ).…”
Section: Therapeutic Approaches To Target Mdsc In Hematological Cancersmentioning
confidence: 76%
“…Using short hairpin constructs against RBP-J, Notch signaling was attenuated in BM cells and this resulted in reduced MDSC suppressive capacity. In addition, injection of RBP-J-deficient MDSC in tumor-bearing mice significantly reduced the tumor growth compared to controls (79,113).…”
Section: Notch Inhibitorsmentioning
confidence: 90%
“…KOPT-K1 [ 47 , 48 ], DND41 [ 10 , 48 ] and U937 [ 49 , 50 ] cells were cultured in RPMI-1640 (21875091; Gibco, Carlsbad, CA, USA), supplemented with 10% fetal bovine serum (FBS) (10270106; Gibco), 1 nmol/L L- glutamine (G7513-100ML; Sigma-Aldrich, St. Louis, MO, USA) and 10 nmol/L penicillin/streptomycin (P0781-100ML; Sigma-Aldrich), while TALL1 [ 48 , 51 ], Loucy [ 52 , 53 ] and THP1 [ 50 , 54 ] cells were maintained in RPMI-1640 (21875091; Gibco) containing 15% FBS (10270106; Gibco), 1 nmol/L L-glutamine (G7513-100ML; Sigma-Aldrich) and 10 nmol/L penicillin/streptomycin (P0781-100ML; Sigma-Aldrich). Cell line details are provided in the database Cellosaurus ( , accessed on 10 October 2022), respectively, with the following accession numbers: KOPT-K1 (CVCL_4965), DND41 (CVCL_2022), TALL1 (CVCL_1736), U937 (CVCL_0007), THP1 (CVCL_0006) and Loucy (CVCL_1380).…”
Section: Methodsmentioning
confidence: 99%
“…Single cell transcriptomic analysis revealed that Jagged/Notch signaling regulates immune cell homeostasis, and treatment with an anti-Jagged1 antibody delayed tumor recurrence in a mouse model [ 108 ]. Conversely, myeloid-derived suppressor cells (MDSCs) can induce Notch signaling in a breast cancer model [ 109 ], while dysregulated Notch signaling induces MDSCs in a mouse model for T-ALL [ 110 ].…”
Section: The Role Of Notch Signaling In the Tumor Microenvironmentmentioning
confidence: 99%